Dziecięce filozofowanie na tle romantycznej wizji szlachetnego dzikusa J.J. Rousseau - Maria Szczepska-Pustkowska (Problemy Wczesnej Edukacji)
The 18th century brought a sequence of outlook changes to Europe. Although contemporary transformations occurred slowly, their scale exceeded the previously circumscribed frame. Interpenetration of various ideas and cultural achievements, as well as “transnational exchange”, supported information for the coming into existence of the first theories of childhood. One of such theories was born thanks to Jean Jacques Rousseau (1712–1778), thanks to which the Enlightenment and the Romanticism discovered the noble savage child immersed in nature. Reflection on the phenomenon of childlike philosophizing conducted exactly from the perspective of this romantic vision of the child is the purpose of this paper.